vision at Hashim bin Hardan Al-Kaabi Al-Dorqi (Journal of the College of Basic Education, 2022)
This study reveals another aspect of the image for Al-Dawraky, which is the meaning, as the study aims to clarify the dimensions, levels and intertwining of the meaning as suggested by the image in its different structural degrees. It is the one that generates the intellectual adoption charged with individual feelings, and this adoption is the one that forms the images and connects them within the framework of the integral unity of the poem and all the artistic works of the poet. Significance, so I named the research the image and the vision instead of the image and the meaning.